The Epital Care Model: A New Person-Centered Model of Technology-Enabled Integrated Care for People With Long Term Conditions - Phanareth, Klaus (JMIR Res Protoc, 2017)
BACKGROUND: There is worldwide recognition that the future provision of health care requires a reorganization of provision of care, with increased empowerment and engagement of patients, along with skilled health professionals delivering services that are coordinated across sectors and organizations that provide health care. Technology may be a way to enable the creation of a coherent, cocreative, person-centered method to provide health care for individuals with one or more long-term conditions (LTCs). It remains to be determined how a new care model can be introduced that supports the intentions of the World Health Organization (WHO) to have integrated people-centered care. OBJECTIVE: To design, pilot, and test feasibility of a model of health care for people with LTCs based on a cocreative, iterative, and stepwise process in a way that recognizes the need for person-centered care, and embraces the use of digital technology. METHODS: The overall research method was inspired by action research and used an agile, iterative approach. In 2012, a living lab was established in a Danish municipality which allowed for the freedom of redesigning health care processes. As the first step, a wide group of stakeholders was gathered to create a layout for the reorganization of services and development of technology, based on established principles for innovative management of people with chronic conditions. The next three steps were (1) a proof of concept in 2012, (2) a pilot study, and (3) a feasibility study from 2013 to 2015, in which a total of 93 chronic obstructive pulmonary disease (COPD) patients were enrolled. Citizens were provided a tablet-based solution for remote follow-up and communication purposes, and access to a 24/7 response and coordination center that coordinated both virtual and face-to-face support for COPD management. In step five the initial model was extended with elements that support continuity of care. Beginning in the autumn of 2013, 1102 frail elderly individuals were included and offered two additional services: an outgoing acute medical team and a local subacute bed function. RESULTS: Based on the findings from the iterative process, and evolving technology and workflow solutions, we propose a robust and feasible model that can provide a framework for developing solutions to support an active life with one or more LTCs. The resulting Epital Care Model (ECM) consists of six stages, and serves as a template for how a digitally-enhanced health service can be provided based on patients’ medical needs. The model is designed to be a proactive, preventive, and monitoring health care system that involves individuals in the management of their own health conditions. CONCLUSIONS: The ECM is in accordance with WHO’s framework for integrated people-centered health services, and may serve as a framework for the development of new technologies and provide a template for future reorganization.